Oxidative cyclization of dialdehydes with alcohols and 1, 3-dicarbonyl compounds under Rh(III)/Cu(II) conditions. Issue 49 (9th December 2015) - Matsuda, Takanori; Suzuki, Kentaro; Abe, Shinya; Kirikae, Haruki; Okada, Noboru
Abstract: For the preparation of 3-alkoxyphthalides from phthalaldehydes and alcohols, a cyclization reaction in the presence of a rhodium(III) catalyst and copper(II) salt is reported. Cyclization of phthalaldehydes also occurs with 1, 3-dicarbonyl compounds under similar conditions to produce 3-substituted phthalides in good yields. An acylrhodium(III) species might be a key intermediate in these cyclization reactions. Graphical abstract: